VD_FINDINFO Décision / 2014 / 18 vom 12. November 2013 - VD Tribunal cantonal (2013)
NON-LIEU, DIFFAMATION, PREUVE LIBÉRATOIRE, INDEMNITÉEN GÉNÉRAL | 173 ch. 2 CP, 173 CP, 319 CPP (CH), 429 al. 1 let. a CPP (CH)